THE INFLUENCE OF FUNCTIONAL VALUES ON BEHAVIORAL INTENTIONS IN STUDENTS - Jamaluddin Jamaluddin; Syaifuddin Syaifuddin; Sofiyan Sofiyan (Journal of Management and Innovation Entrepreneurship (JMIE), 2026)
The low level of student trust in a product is caused by various factors. Although various studies have examined the factors that influence consumer behavioral intentions, there is still limited research that specifically explains the role of functional value in shaping students' behavioral intentions as digital-native consumers in the context of higher education in Indonesia. The low level of student trust in a product is caused by various factors. This study aims to examine the influence of functional value on students' behavioral intentions. This type of research is included in the associative or causal research category. The researchers selected 385 students from five universities. The data collection technique used was a questionnaire method, and the measurement scale in this study was a Likert scale with gradations from lowest to highest. The data analysis technique used was statistical analysis, namely the partial least squares structural equation model (PLS SEM). The results showed that functional value directly had a positive and significant influence on behavioral intentions, with a coefficient value of 0.410, indicating that the fifth hypothesis was accepted. This finding confirms the dominance of utilitarian considerations in shaping students' behavioral intentions as digital-native consumers.